PRIVACY ON UNIVERSITY STUDENT IN ASRAMA ADVENT INDONESIA UNIVERSITY (UNAI) BANDUNG DORMITORY: A CASE STUDY - Nelly Dumauli Pardede; Hendro Prabowo (Universitas Gunadarma, 2007)
It’s easy to find different hostel based on facility and environment. There is choice a house with a few rooms and single washroom, single kitchen, and single living room. But mostly is in hostel type, a big building with many rooms. We can find different type of room in big building, such as a room furnish with washroom, or few rooms with single washroom, or even many rooms in the same level with single washroom. Student living there comes from different race and culture. To be convenient, every occupant is accused to adapt suitably with others and its environment. The main problem of living in hostel is privacy matter. To be capable to help someone with privacy problem, we need to know “the intended privacy for student and privacy mechanism in a hostel.” With that information, it’s expected that hostel owner capable to build a better one so that occupants feel convenient to be living inside. The objective of this research is to explore privacy problem and behavior mechanism among University of Indonesia Advent students. Method which was used is qualitative method with case study approach. The steps performed on this case study were interview, observation, behavior map, and documentation. Result shows that subject didn’t manifest privacy problem because he/she has experienced of living in the same environment since secondary school. In this case, subject performed privacy mechanism in forms of verbal behavior, cultural and territorial. Key words: privacy, hostel